Comparison and Evaluation of the Efficacy of Sesame Oil, Coconut Oil, and Sunflower Oil Pulling on Gingival Health—A Triple-Blind Randomized Clinical Trial - Meghna Mehta; Prasanta Majumder; Dibyendu Dam Chowdhury; Praveen Kalai; K. Mohamed Adhil; Shib Kumar Nath (Journal of Pharmacy and Bioallied Sciences)
Objective: Compare and evaluate the efficacy of sesame oil, coconut oil, and sunflower oil pulling on gingival health. Methodology: Triple-blind randomized clinical trial was conducted by using three different oils in three groups. Results: All three oils were found to be effective on gingival health but coconut oil is found to be more effective. Conclusion: This study concluded that all three oils were effective in improving gingival health.